(untitled) (Acta Polytechnica CTU Proceedings, 2018)
Ground anchors represent an important structural element in the area of geotechnical engineering. Despite their extensive usage, a design process of these elements is usually performed using simple empirical and semi-empirical methods, neglecting several important influencing factors. This paper gives an analysis of the factor of non-uniform distribution of skin friction resulting in a progressive failure of ground anchors. First, the finite element method in combination with a material model involving regularized strain softening is utilized. Next, an experimental program, including several investigation anchor load tests, was carried out. The goal of this program was to confirm preliminary conclusions drawn from numerical studies and to obtain relevant data for further back analysis. After, there is then described a newly developed application based on the load transfer method, in which all the findings from numerical computations and experimental measurements are incorporated.